Curricula, attributes and clinical experiences of radiography programs in four European educational institutions - Sá dos Reis, Cláudia; Pires Jorge, J.; York, H.; Flaction, L.; Johansen, S.; Maehle, S. (W.B. Saunders Co. Ltd., 2018)
Introduction: The aim of this study was to compare radiography curricula, teaching/learning strategies, skill development, clinical practice outcomes and research development delivered by four European educational institutions. Methods: This study was carried out in two phases: the first focused on curricula analysis; the second involved online questionnaires to ascertain data from two key-informants: students who had recently completed their bachelor thesis and teaching-staff. Questionnaires were designed to capture teaching and learning strategies, skill acquisition and outcomes of clinical practice and research. Descriptive statistics and thematic analysis were performed according to the nature of the questions. Results: The European Credits Transfer System dedicated per core subject area (natural sciences, clinical practice, research, imaging technology, humanities) differed between institutions. Students classified technical, practical and communication skills as the most important, teaching-staff highlighted also critical thinking. The students defined as “very good” their experience in radiography (58.5%) and computed-tomography (45%). Magnetic resonance imaging practice was considered “Average” by 53% of the UK-students and “Good” by the other European students (40%). According to 71% (55/78) of the students, research work contributed to the development of critical/reflective thinking. Conclusions: The four radiography programs presented variations in curricula, contact-hours, clinical experience and outcomes. Research units allowed the participant-students to develop their critical thinking capabilities. The outcomes from clinical practice differ across the institutions, mainly due to differences in background and access to specialities. Further work is necessary to assess the real impact of different radiography programs on professional and academic mobility across Europe.